Individual pulse monitoring and dose control system for pre-clinical implementation of FLASH-RT. (7th May 2022) - Ashraf, M Ramish; Rahman, Mahbubur; Cao, Xu; Duval, Kayla; Williams, Benjamin B; Jack Hoopes, P; Gladstone, David J; Pogue, Brian W; Zhang, Rongxiao; Bruza, Petr
Abstract: Objective. Existing ultra-high dose rate (UHDR) electron sources lack dose rate independent dosimeters and a calibrated dose control system for accurate delivery. In this study, we aim to develop a custom single-pulse dose monitoring and a real-time dose-based control system for a FLASH enabled clinical linear accelerator (Linac). Approach. A commercially available point scintillator detector was coupled to a gated integrating amplifier and a real-time controller for dose monitoring and feedback control loop. The controller was programmed to integrate dose for each radiation pulse and stop the radiation beam when the prescribed dose was delivered. Additionally, the scintillator was mounted in a solid water phantom and placed underneath mice skin for in vivo dose monitoring. The scintillator was characterized in terms of its radiation stability, mean dose-rate ( D ̇ m ), and dose per pulse ( D p ) dependence. Main results. The D p exhibited a consistent ramp-up period across ∼4–5 pulse. The plastic scintillator was shown to be linear with D ̇ m (40–380 Gy s −1 ) and D p (0.3–1.3 Gy Pulse −1 ) to within +/− 3%. However, the plastic scintillator was subject to significant radiation damage (16%/kGy) for the initial 1 kGy and would need to be calibrated frequently. Pulse-counting control was accurately implemented with one-to-one correspondence between the intended and the actual delivered pulses. The dose-based control was sufficient to gate on any pulse of the Linac. In vivo dosimetry monitoring with a 1 cm circular cut-out revealed that during the ramp-up period, the average D p was ∼0.045 ± 0.004 Gy Pulse −1, whereas after the ramp-up it stabilized at 0.65 ± 0.01 Gy Pulse −1 . Significance. The tools presented in this study can be used to determine the beam parameter space pertinent to the FLASH effect. Additionally, this study is the first instance of real-time dose-based control for a modified Linac at ultra-high dose rates, which provides insight into the tool required for future clinical translation of FLASH-RT.